2022
DOI: 10.3389/fphar.2022.861782
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Antibiotic Prescriptions in Chinese Primary Health Care and the Impact of the COVID-19 Pandemic: A Typically Descriptive and Longitudinal Database Study in Yinchuan City

Abstract: Background: The appropriateness of antibiotic prescriptions in primary care has not been well evaluated in China in recent years. Furthermore, the impact of coronavirus disease 2019 (COVID-19) on antibiotic prescriptions has not yet been investigated in China. We aimed to assess the appropriateness of antibiotic prescriptions and to evaluate the potential association between the COVID-19 pandemic and antibiotic prescriptions in primary care settings of Yinchuan, a city in China.Methods: This study included 155… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 48 publications
(133 reference statements)
1
16
0
Order By: Relevance
“…Especially, the number of prescriptions of certain categories of antibacterials (e.g., third-generation cephalosporins, fluoroquinolones) decreased significantly [ 11 , 12 , 14 16 ]. Similarly, several studies in China also found that there was a decline antibiotic consumption during the COVID-19 pandemic [ 17 19 ]. For example, a study from Yinchuan of China showed that the decrease in inappropriate antibiotic prescriptions in primary care settings may be associated with the COVID-19 pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Especially, the number of prescriptions of certain categories of antibacterials (e.g., third-generation cephalosporins, fluoroquinolones) decreased significantly [ 11 , 12 , 14 16 ]. Similarly, several studies in China also found that there was a decline antibiotic consumption during the COVID-19 pandemic [ 17 19 ]. For example, a study from Yinchuan of China showed that the decrease in inappropriate antibiotic prescriptions in primary care settings may be associated with the COVID-19 pandemic [ 19 ].…”
Section: Introductionmentioning
confidence: 88%
“…The Coronavirus Disease-19 (COVID-19) pandemic swept across the world quickly and placed a heavy burden on the health systems globally. The impacts of the COVID-19 pandemic on antibiotic consumption and the risk of AMR have become a concern of many researchers of antibiotic resistance [ 11 19 ]. According to a report, after the outbreak of the COVID-19 pandemic in most European countries, the total consumption of antibiotics declined by more than 15%, which was mainly observed in PHSs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Coronavirus Disease-19 (COVID-19) pandemic swept across the world quickly and placed a heavy burden on the health systems globally. The impacts of the COVID-19 pandemic on antibiotic consumption and the risk of AMR have aroused the attention of many researchers of antibiotic resistance [11][12][13][14][15][16][17][18][19]. A report stated that after the outbreak of the COVID-19 pandemic in most European countries, the total consumption of antibiotics declined by more than 15%, which was mainly observed in PHSs [13].…”
Section: Introductionmentioning
confidence: 99%
“…In China, a few similar studies also found that there was a decline in consumption of antibiotics during the . For example, a study from Yinchuan, China showed that the decrease in inappropriate antibiotic prescriptions in primary care settings may be associated with the COVID-19 pandemic [19]. It can be seen that the antibiotic use pattern may have changed greatly during the COVID-19 pandemic, but currently, there is no adequate evidence for the changes in antibiotic consumption in PHSs in China.This study aimed to assess the immediate and long-term impacts of the COVID-19 pandemic on the changes in antibiotic consumption in PHSs in Shandong, China.…”
mentioning
confidence: 99%
See 1 more Smart Citation